What's on your mind? a visual portrayal of the social life of a wallflower - Fabella, Danielle Tamara Basila
Amidst an increasingly social global environment, the wallflower remains largely left out. A general impression about wallflowers is that they are strange of weird for having mostly no friends or social circles. In 1999, Stephen Chbosky published his novel "The Perks of Being a Wallflower" which was eventually adapted into film in 2012. Chbosky tells the story of a young teen struggling with social interaction and coming to terms with life growing up. Both the novel and the film helped popularize the use of the term "wallflower" to refer to someone who has difficulty socializing with others. They helped direct the wallflower, ironically so, into the social spotlight, as more and more people began associating themselves with this obscure label.